2002
DOI: 10.5713/ajas.2002.346
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Profiles during Periparturient Period in Single and Twin Fetus Bearing Goats

Abstract: The effect of fetal number (single or twin) on plasma concentrations of progesterone, estradiol 17β, cortisol, prolactin, growth hormone, triiodothyronine, thyroxine and insulin around parturition (periparturient period) were studied on ten Alpine × Beetle crossbred goats in their first to third lactation. The hormone profiles were studied on days -20, -15, -10, -5, -4, -3, -2, -1 prior to kidding and on day 0 and +1, +2, +3, +4, +5, +10, +15, +20 days postkidding. Plasma progesterone levels were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
7
15
0
1
Order By: Relevance
“…Nevertheless, more from the body reserves fulfills the maintenance energy requirements of the goat. As previously stated, we observed that this mobilization is concentrated in the final third of pregnancy (Khan and Lundri, 2002), which can be verified by the increasing levels of serum NEFA and ß-hydroxybutyrate during this phase.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, more from the body reserves fulfills the maintenance energy requirements of the goat. As previously stated, we observed that this mobilization is concentrated in the final third of pregnancy (Khan and Lundri, 2002), which can be verified by the increasing levels of serum NEFA and ß-hydroxybutyrate during this phase.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, greater (P<0.01) concentration of insulin was reported in nonlactating than in lactating ewes (Hatfield et al 1999). The results of the present study are in general agreement with Khan and Ludri (2002) who reported low plasma insulin concentrations on the day of kidding in goats.…”
Section: Resultssupporting
confidence: 82%
“…T 4 levels were found to be low during the early lactation period in cows with severe fatty liver (Stojic et al 2001). The lowest levels of plasma T 4 on the day of kidding compared to postpartum period have been reported by Khan and Ludri (2002). The results of the present study are in accordance to those of Rasooli et al (2004) who observed that cold environment may be a stimulus to increase the thyrotrophic hormone output thereby resulting in a higher concentration of thyroid hormone in serum.…”
Section: Thyroxine (T 4 )supporting
confidence: 82%
“…Prepartum surge in estrogen on day of kidding is essential for starting parturition, i.e., uterine contraction and providing sympathetic stimulus for oxytocin and triggering prostaglandin release for myometrial contraction. However, low level of estrogen was reported in twin pregnancy as compared to singlet pregnancy in crossbred goats [ 28 ]. The decline in progesterone concentration is physiological due to the destruction of the corpus luteum of pregnancy and the decreased level of progesterone released from the placenta [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%